The Mediation Role of Purchase Intention on The Relationship Between Social Media Marketing, Brand Image, and Brand Loyalty: A Case Study of J&T Express Indonesia - Thomas Sadli; Vincentius Christianto Hartono; Adelina Proboyo (Master of Management, School of Business and Management, Petra Christian University, 2022)
The competition in Indonesia's courier, express, and parcel market has been very tight. J&T Express, one of the courier companies in Indonesia, needs to improve itself to survive and gain more market share. The research aims to analyze the impact of social media marketing and brand image on purchase intention and brand loyalty. The research also wants to determine the role of purchase intention in mediating the impact of social media marketing and brand image on brand loyalty. Data from 104 respondents who have ever used the service of J&T Express and watched the content of J&T's social media content were collected and analyzed using PLS-SEM. The result shows that social media marketing, brand image, and purchase intention significantly influence brand loyalty. However, purchase intention is proven not to mediate the relationship between social media marketing and purchase intention due to the insignificance of social media marketing on purchase intention. On the other hand, purchase intention significantly mediates the impact of brand image on brand loyalty.